2017
DOI: 10.1016/j.appet.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' feeding practices and children's weight status in Mexican American families

Abstract: Mothers’ feeding practices are associated with their children’s weight status, but little is known about the associations between fathers’ feeding practices and children’s weight status. Moreover, there is a dearth of research on Latino fathers’ feeding practices and children’s weight status, even though Latino children suffer some of the highest obesity rates in the U.S. We examined the associations between fathers’ feeding practices and child weight status, conditional on mothers’ feeding practices, within 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 57 publications
1
42
0
6
Order By: Relevance
“…A similar number of studies, however, reported no differences in the types and levels of food parenting practices used by mothers and fathers 66‐74 . When looking at the influence of fathers' food parenting on child outcomes, studies reported that fathers' use of controlling food parenting practices is linked with higher consumption of unhealthy foods or higher rates of overweight among children 29,63,75‐78 and their use of responsive food parenting practices, such as modeling healthy eating behaviors, is linked with positive diet and weight outcomes in children 76,78‐80 . Three studies reported no effects of fathers' food parenting on children's outcomes 81‐83 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar number of studies, however, reported no differences in the types and levels of food parenting practices used by mothers and fathers 66‐74 . When looking at the influence of fathers' food parenting on child outcomes, studies reported that fathers' use of controlling food parenting practices is linked with higher consumption of unhealthy foods or higher rates of overweight among children 29,63,75‐78 and their use of responsive food parenting practices, such as modeling healthy eating behaviors, is linked with positive diet and weight outcomes in children 76,78‐80 . Three studies reported no effects of fathers' food parenting on children's outcomes 81‐83 …”
Section: Resultsmentioning
confidence: 99%
“…The lack of emphasis on fathers in obesity and food parenting research is concerning given sociocultural shifts in fathers' involvement in child rearing, 22‐24 with a threefold increase in the time fathers engage in child care activities since 1965, 25 and consistent evidence of the beneficial effects of engaged fathers on all areas of child development 26‐29 . Moreover, national data on fathers' involvement with their children (2006‐2010) indicate that the majority of fathers who live with their children are involved in food parenting with 72% feeding their children (under 5 years) and 66% eat meals with their children (5‐12 years) on a daily basis 30…”
Section: Introductionmentioning
confidence: 99%
“…None the less, these studies underscore father's influential role on children's eating (36)(37)(38)(39)(40) . This small body of research indicates the need for further research, but also suggests that Latino fathers be included in nutrition interventions designed to reduce and prevent child obesity (36)(37)(38)(39)(40) . Similarly, a growing research literature documents the influential role of fathers on children's PA and SB, but the majority of this research has focused on Caucasian, middle-income fathers (39,41) with limited research examining Latino fathers' beliefs, attitudes and practices related to young children's PA and SB (39,41) .…”
mentioning
confidence: 91%
“…Fathers play an important role in caring for young children—especially when it comes to feeding behaviours 4,7,15‐20 . Paternal feeding practices have been associated with childhood obesity in children aged 8 to 10 years, even after accounting for maternal feeding practices 19 . In a study of pre‐schoolers, more controlling fathers had daughters with a higher percentage of body fat 17 .…”
Section: Introductionmentioning
confidence: 99%